The Assyrians in Australian archives (Piscataway, NJ)
xiv, 505 sayfa
Keywords: “The small Assyrian community proved to be loyal, dedicated and hard-working citizens of Australia during the years 1914–1947. For the first time the Assyrian issue will be seen through the eyes of Australian official documents and it is hoped that this monograph will raise awareness of these people within Australia and abroad“ -- Yayıncı.